Korelasi Pemahaman Materi Tanggung Jawabku terhadap Keluarga dengan Karakter Menghormati Orang Tua oleh Siswa Kelas XI SMK Negeri 2 Balige Tahun Pembelajaran 2023/2024 - Jonathan Horas M Silaban; Lustani Samosir; Grecetinovitria M. Butar-Butar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to determine the relationship between Understanding the Material of My Responsibility Towards the Family with the Character of Respecting Parents by Class XI Students of SMK Negeri 2 Balige Learning Year 2023/2024. The method used in the research is quantitative method with inferential statistical data analysis. The population is all XI grade students of SMK Negeri 2 Balige in the 2023/2024 academic year who are Christian as many as 300 people and a sample of 60 people is determined which is taken from each department 20% using random sampling. Data were collected using 22 items for variable X and a positive closed questionnaire of 20 items for variable Y. The results of data analysis show that there is a relationship between Understanding the Material of My Responsibility Towards the Family with the Character of Respecting Parents by Class XI Students of SMK Negeri 2 Balige Learning Year 2023/2024: with rxy = 0.665> 0.254 from rtabel(ɑ=0.05; IK=95%; n=60) andtcount = 6.781> 2.000 from ttable(ɑ=0.05; dk=n-2 = 58) thus there is a positive and significant relationship between variable X and variable Y. ThenHa is accepted and H0 is rejected.